(untitled) (Research, Society and Development, 2026)
University life presents many difficulties, and students initially believe that, because they are studying a subject of interest, they will not face any adversity. However, they may encounter financial problems, difficulties in relationships with professors and colleagues, among others. Despite these adversities, it is important to understand why some students drop out and abandon their courses, while others remain in their studies and manage to graduate. One way to understand this phenomenon is through academic resilience. Academic resilience is the ability of students to overcome adversities related to the academic environment and to evaluate aspects related to remaining in the school environment and how they achieve their academic goals. The aim of this work is to present the process of translation and adaptation of the Academic Resilience Scale (ARS-30) for university students in Paraná. For the validity process of the scale, 458 students, enrolled in six undergraduate courses from three Higher Education Institutions in the State of Paraná, have participated. The scale was translated, back-translated by a fluent English translator, and analyzed by three judges with suggested changes. Factorial and exploratory analysis was performed, and data similar to the original scale were found. Cronbach’s alpha values ​​were satisfactory, and convergent and discriminant validity were confirmed. The data found indicate the importance and possibility of using the Academic Resilience Scale (ERA) both for diagnosing strengths and weaknesses in coping with adversity, as well as assisting in the implementation of intervention projects.